Hippocampal Pathology in the Human Neuronal Ceroid‐Lipofuscinoses: Distinct Patterns of Storage Deposition, Neurodegeneration and Glial Activation - Tyynelä, Jaana (Brain Pathol, 2006)
The neuronal ceroid‐lipofuscinoses (NCLs) are recessively inherited lysosomal storage diseases, currently classified into 8 forms (CLN1‐CLN8). Collectively, the NCLs constitute the most common group of progressive encephalopathies of childhood, and present with visual impairment, psychomotor deterioration and severe seizures. Despite recent identification of the underlying disease genes, the mechanisms leading to neurodegeneration and epilepsy in the NCLs remain poorly understood. To investigate these events, we examined the patterns of storage deposition, neurodegeneration, and glial activation in the hippocampus of patients with CLN1, CLN2, CLN3, CLN5 and CLN8 using histochemistry and immunohistochemistry. These different forms of NCL shared distinct patterns of neuronal degeneration in the hippocampus, with heavy involvement of sectors CA2‐CA4 but relative sparing of CA1. This selective pattern of degeneration was also observed in immunohistochemically identified interneurons, which exhibited a graded severity of loss according to phenotype, with calretinin‐positive interneurons relatively spared. Furthermore, glial activation was also regionally specific, with microglial activation most pronounced in areas of greatest neuronal loss, and astrocyte activation prominent in areas where neuronal loss was less evident. In conclusion, the NCLs share a common pattern of selective hippocampal pathology, distinct from that seen in the majority of temporal lobe epilepsies.